(untitled) (Texas Journal of Multidisciplinary Studies, 2024)
On the basis of the foregoing, the current research came to test the relationship between organizational trust, administrative transparency and work outputs in a sample of physical education teachers in the schools of the Dhi Qar governorate center, and the aim of this research is to study the impact relationship and verify the size of the interactive impact of organizational trust as an intermediate variable on the relationship the research was conducted The most important recommendations are to focus on internal working conditions by working on establishing solid rules to enhance their levels and the level of work and their awareness by teachers by building an organizational culture based on the development of physical and psychological work requirements and building a wide portfolio of transparent practices that reflect the needs of the teachers and the to trust teachers and direct their behavior in a positive direction, which is considered to be important indicators in the quality of performance